3D hand pose and shape estimation from RGB images for keypoint-based hand gesture recognition. (September 2022) - Avola, Danilo; Cinque, Luigi; Fagioli, Alessio; Foresti, Gian Luca; Fragomeni, Adriano; Pannone, Daniele
Highlights: presentation of a comprehensive end-to-end keypoint framework for 3D hand pose/shape estimation. design of a multi-task feature extractor, optimized viewpoint encoder, and re-projection procedure for stable outputs. evaluation on a second task, i.e., hand-gesture recognition, where other keypoint-based approaches are outperformed. Abstract: Estimating the 3D pose of a hand from a 2D image is a well-studied problem and a requirement for several real-life applications such as virtual reality, augmented reality, and hand gesture recognition. Currently, reasonable estimations can be computed from single RGB images, especially when a multi-task learning approach is used to force the system to consider the shape of the hand when its pose is determined. However, depending on the method used to represent the hand, the performance can drop considerably in real-life tasks, suggesting that stable descriptions are required to achieve satisfactory results. In this paper, we present a keypoint-based end-to-end framework for 3D hand and pose estimation and successfully apply it to the task of hand gesture recognition as a study case. Specifically, after a pre-processing step in which the images are normalized, the proposed pipeline uses a multi-task semantic feature extractor generating 2D heatmaps and hand silhouettes from RGB images, a viewpoint encoder to predict the hand and camera view parameters, a stable hand estimator to produce the 3D hand pose and shape, and a loss function to guide all of the components jointly during the learning phase. Tests were performed on a 3D pose and shape estimation benchmark dataset to assess the proposed framework, which obtained state-of-the-art performance. Our system was also evaluated on two hand-gesture recognition benchmark datasets and significantly outperformed other keypoint-based approaches, indicating that it is an effective solution that is able to generate stable 3D estimates for hand pose and shape.